Tanggungjawab dan Akibat Hukum bagi Notaris yang Membuat Perjanjian Pinjam Nama (Nominee) - santi; Arsin Lukman (Faculty of Law, University of Mataram, 2023)
Ownership of land rights in Indonesia could solely owned by Indonesian citizens or legal entities which determined by the Indonesian Government. Based on the practice, there are lots of legal smuggling in the making of a nominee agreement by a Notary. The nominee agreement is a name-borrowing agreement, which commonly consist of the foreign citizens measures in borrowing the names of Indonesian citizens to conduct sale and purchase transactions for proprietary land. Through the nominee agreement, it is stipulated that the status of the land in the land book and certificate of property rights is registered in the name of an Indonesian citizen, yet the ownership or control remains with a foreign citizen. This study aims to examine the validity of the nominee agreement as a form of foreign ownership at once to find out the form of responsibilities and legal consequences for the concerned Notary whose composed the nominee agreement. This research refers to the Decision Number 45/Pdt.G/2020/PNTpg. It uses normative legal research methods, and the type of approach to case legislation is in the form of decisions. Based on the results of this study, it is shows that there are lots of legal smuggling in the making of a nominee agreement by a Notary. The nominee agreement has indirectly violated the provisions of Article 26 Paragraph (2) of Law Number 5 of 1960, since there has been a transfer of ownership in the form of property rights to foreign citizens, and as confirmed on Article 21 Paragraph (1) of Law Number 5 of 1960, only Indonesian citizens have the right to own property rights. As known, foreign citizen may only have usufructuary rights and rental rights. Therefore, the nominee agreement has no legal force at all.